Effects of acupressure on sleep quality and anxiety of patients with second- or third-degree burns: a randomized sham-controlled trial - Zahra Salajegheh; Mehdi Harorani; Mohadese Shahrodi; Elahe Dolati; Mahtab Farahani; Nazanin Amini; Danial Habibi (BMC, 2024)
Abstract Background Although acupressure is proposed to boost sleep quality and alleviate anxiety in various disorders, no trials have yet documented these consequences in burn victims. Considering the high importance of managing sleep quality and anxiety among burn patients utilizing adjunctive non-pharmacological measures, this study sought to investigate the impacts of acupressure on sleep quality and anxiety among a population of Iranian patients with burn injuries. Methods This trial was performed on 72 patients with second- or third-degree burns, who were divided into two equal arms to receive routine care plus 10-minute acupressure on either real acupoints (i.e., Yintang and Shen men) or sham points for three consecutive nights. Sleep quality and anxiety were investigated at baseline (T1) and on the fourth day (T2) by using St. Mary's Hospital Sleep Questionnaire (SMHSQ) and Spielberger's State-Trait Anxiety Inventory for State Anxiety (STAI-S), respectively. Results The mean scores of SMHSQ and STAI-S were significantly lower in the real acupressure arm at T2 (P < 0.001 in two cases), implying better sleep quality improvement and higher anxiety alleviation. Also, the reduction in mean changes of SMHSQ and STAI-S scores from T1 to T2 was significantly more in the real acupressure arm (P < 0.001 in two cases). Conclusion Acupressure, as a low-cost complementary method, could be potentially helpful in enhancing sleep quality and decreasing the anxiety of burn patients. Additional long-term trials are required to identify the sustainability of the findings. Trial Registration No IRCT20130424013110N13 (Registration date: 19/03/2021, https://www.irct.ir/trial/55076 ).